Emerging Paradigms for Development Planning: A Case of Thrissur, the Cultural Capital of Kerala. (2016) - Devika, K.C.; Ranjini Bhattathiripad, T.; Kothari, Bejene S.
Abstract: Thrissur, renowned as the cultural capital of Kerala is a city with a strong legacy of cultural, historic and traditional aspects. It is one of its kind in Kerala with a well-planned ring and radial pattern of development. The paper presents an overview of various aspects of the city development such as history, culture, heritage, geography, environment, demography and trade & commerce based on secondary sources. The growth of the city with respect to its development phases and emerging issues are also discussed. General recommendations for improvement of the city are suggested with regard to the current situation.